The effect of radio-collar weight on survival of migratory caribou - Couturier, Serge; Festa-Bianchet, Marco; Côté, Steeve D.; Rasiulis, Alexandre (The Journal of Wildlife Management, 2020)
Radio transmitters are widely used in wildlife management; therefore, it is essential to assess any effects that they may have on animal survival. We compared the survival of 269 randomly selected adult migratory caribou (Rangifer tarandus) fitted with either light very high frequency or heavy Argos satellite collars during the same period. Heavy collars reduced annual survival of caribou in a declining population with generally poor body condition by about 18%. Accurate estimates of survival are crucial for management decisions and possible effects of collars should be considered when calculating estimates.